Developing an e-module to learn addition and substraction using Genially for students with special needs - Jannah, Miftahul; Istiandaru, Afit (International Journal on Education Insight, 2024)
Deaf children have auditory limitations and therefore rely more heavily on visual cues in their daily lives. For this reason, there is a need for media that can visualize mathematical concepts or materials. The aim of this study is to develop a learning modul for addition and subtraction topics and to assess the validity and practicality of the developed electronic module. We used the ADDIE R&D model which consists of five stages—analysis, design, development, implementation, and evaluation. We developed the e-module using Genially platform. The validity of the module was assessed by experts in mathematics education and inclusive education. Then, we tried out the module to seven fifth-grade deaf students at SLB Negeri 2 Bantul—a public school for students with special needs. The result of the validation by content experts got an average score of 4.2 (good), the validation by media expert got an average score of 4.16 (good), and the validation by teacher got an average score of 4.38 (very good). Moreover, the practicality testing got the average score of the students’ response at 4.2 (small group) and 4.33 (field testing), which means the module is practical.